Konsep dan Sumber Hukum: Analisis Perbandingan Sistem Hukum Islam dan Sistem Hukum Positif - M. Taufiq (Program Pascasarjana Universitas Ibrahimy, 2021)
The definition of positive law was law in the form of laws that regulate the relationship between humans and humans, or with legal entities, while the understanding of Islamic law was a system of 'obligations' and 'prohibitions' rather than specific laws. Islamic law was broadly defined by rules which were the result of understanding and deduction from the provisions revealed by Allah SWT to the Prophet Muhammad SAW. Therefore, the main sources of Islamic law were the Qur'an and Hadith. source of pure positive law from society. This was due to the retrieval or discovery of positive law using the inductive method. That was by observing the actions and attitudes of community members. From these observations, general regulations that bind the whole community were made. In this article, the author tried to explain further the analysis of the concepts and sources of the two laws, and their comparative analysis